(untitled) (KULT_online, 2013)
The anthology Soziale Gedächtnisse. Selektivität in Erinnerungen an die Zeit des National- sozialismus contains research articles from a study funded by the German Research Foundation (the DFG). The authors argue against stark divisions between communicative and cultural memory once introduced by Jan Assman. Using not only narrative interviews, but also family conversation to analyse memories during the time of the Nazis, the evaluation is both topical and sequence-oriented. The aim of this volume is to close the academic void when it comes to considering the selectivity of memories.